How societies are born : governance in West Central Africa before 1600 - Vansina, Jan (ACLS Humanities E-Book., 2004)
Like stars, societies are born, and this story deals with such a birth. It asks a fundamental and compelling question: how did societies first coalesce from the small foraging communities that had roamed in West Central Africa for many thousands of years?